Peran Mahasiswa Ekonomi Islam dalam Kontribusi Operasional di Kelurahan Tarok Dipo Kota Bukittinggi - Annisa Lubis (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to explore the role of Islamic economics students in operational contributions in Tarok Dipo Village, Bukittinggi City. Students, as agents of change, have significant potential to improve community welfare through the application of Islamic economic principles. In this context, this study used a qualitative approach using interviews and observation methods to identify initiatives taken by students in local economic empowerment programs. The results indicate that students play an active role in various activities, such as entrepreneurship training, local product development, and outreach on Islamic financial management. These contributions not only improve community skills but also strengthen Islamic economic values ​​at the local level. Furthermore, collaboration between students, the government, and the community is key to the success of these programs.